Potential of conservation agriculture modules for energy conservation and sustainability of rice-based production systems of Indo-Gangetic Plain region - Nandan, Rajiv; Poonia, Shish Pal; Singh, Sati Shankar; Nath, Chaitanya Prasad; Kumar, Virender; Malik, Ram Kanwar; McDonald, Andrew; Hazra, Kali Krishna (Springer, 2021)
Rice-based cropping systems are the most energy-intensive production systems in South Asia. Sustainability of the rice-based cropping systems is nowadays questioned with declining natural resource base, soil degradation, environmental pollution, and declining factor productivity. As a consequence, the search for energy and resource conservation agro-techniques is increasing for sustainable and cleaner production. Conservation agriculture (CA) practices have been recommended for resource conservation, soil health restoration and sustaining crop productivity. The present study aimed to assess the different CA modules in rice-based cropping systems for energy conservation, energy productivity, and to define energy-economic relations. A field experiment consisted of four different tillage-based crop establishment practices (puddled-transplanted rice followed by (fb) conventional-till maize/wheat (CTTPR-CT), non-puddled transplanted ricefbzero-till maize/wheat (NPTPR-ZT), zero-till transplanted ricefbzero-till maize/wheat (ZTTPR-ZT), zero-till direct-seeded ricefbzero-till maize/wheat (ZTDSR-ZT)), with two residue management treatments (residue removal, residue retention) in rice–wheat and rice–maize rotations were evaluated for energy budgeting and energy-economic relations. Conservation-tillage treatments (NPTPR-ZT, ZTTPR-ZT, and ZTDSR-ZT) reduced the energy requirements over conventional tillage treatments, with the greater reduction in ZTTPR-ZT and ZTDSR-ZT treatments. Savings of energy in conservation-tillage treatments were attributed to reduced energy use in land preparation (69–100%) and irrigation (23–27%), which consumed a large amount of fuel energy. Conservation-tillage treatments increased grain and straw/stover yields of crops, eventually increased the output energy (6–16%), net energy (14–26%), energy ratio (25–33%), and energy productivity (23–34%) as compared with CTTPR-CT. For these energy parameters, the treatment order was ZTDSR-ZT ≥ ZTTPR-ZT > NPTPR-ZT > CTTPR-CT (p < 0.05). Crop residue retention reduced net energy, energy ratio, and energy productivity when compared with residue removal. Our results of energy-economic relations favored the “conservative hypothesis,” which envisages that energy and monetary investments are not essentially the determinants of crop productivity. Thus, zero tillage-based crop establishments (ZTTPR-ZT, ZTDSR-ZT) in rice-based production systems could be the sustainable alternative to conventional tillage-based agriculture (CTTPR-CT) as they conserved non-renewable energy sources, reduced water requirement, and increased crop productivity.